Anodal transcranial direct current stimulation of the right dorsolateral prefrontal cortex impairs long-term retention of reencountered memories. (November 2018) - Marián, Miklós; Szőllősi, Ágnes; Racsmány, Mihály
Abstract: Repeated encounter with encoded memories is often a fundamental component of long-term learning processes, however, the role of repeated access to encoded memories in long-term consolidation is yet to be clarified. Here we investigated whether the long-term retention of newly acquired associative memories is affected if one of the central areas of the attentional control network is stimulated before or after repeated access to acquired information. Non-clinical participants (undergraduate students, N = 118) were exposed to an associative verbal learning task. Following the initial learning of word pairs, memories for the word pairs were reencountered either by re-presenting the stimuli to the participants for restudying or by cued recall. The reencounter phase was either preceded by (Experiment 1) or followed by (Experiment 2) anodal transcranial Direct Current Stimulation of the right dorsolateral prefrontal cortex. Memory retention was assessed seven days after the reencounter phase. When we measured successful access to learned paired-associates in the reencounter phase, there was no difference between the anodal and sham stimulation condition in either Experiment 1 or 2. However, and importantly, anodal stimulation had a detrimental impact on long-term memory but only when stimulation preceded the reencountering of memories (in Experiment 1). Our results suggest that stimulation of the so-called control network during repeated access to acquired information disrupts the long-term retention of these memories. These findings are in line with earlier results showing that repeated access to learned information systematically decreases the involvement of control processes in retrieval and presumably promotes learning through the automatization of cue-target association. At a neural level, a possible substrate of repeated memory reencountering is a shift in frontohippocampal connectivity.